The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/s1930297500005611
|View full text |Cite
|
Sign up to set email alerts
|

The average laboratory samples a population of 7,300 Amazon Mechanical Turk workers

Abstract: Using capture-recapture analysis we estimate the effective size of the active Amazon Mechanical Turk (MTurk) population that a typical laboratory can access to be about 7,300 workers. We also estimate that the time taken for half of the workers to leave the MTurk pool and be replaced is about 7 months. Each laboratory has its own population pool which overlaps, often extensively, with the hundreds of other laboratories using MTurk. Our estimate is based on a sample of 114,460 completed sessions from 33,408 uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(33 citation statements)
references
References 28 publications
0
32
1
Order By: Relevance
“…The present studies also relied on participants recruited through Mturk. Recent work has noted that Mturk participants may have prior experience with canonical judgment and decision-making tasks (Stewart et al, 2015), and this experience may influence the strength of different experimental manipulations (Chandler, Paolacci, Peer, Mueller & Ratliff, 2015;Rand et al, 2014). However, we believe that task experience would -if anything -reduce the differences we observed in the present studies.…”
Section: Limitationscontrasting
confidence: 52%
“…The present studies also relied on participants recruited through Mturk. Recent work has noted that Mturk participants may have prior experience with canonical judgment and decision-making tasks (Stewart et al, 2015), and this experience may influence the strength of different experimental manipulations (Chandler, Paolacci, Peer, Mueller & Ratliff, 2015;Rand et al, 2014). However, we believe that task experience would -if anything -reduce the differences we observed in the present studies.…”
Section: Limitationscontrasting
confidence: 52%
“…Across seven studies conducted by Berinsky and colleagues (2012) with over 1,500 unique subjects, 30% of subjects had participated in more than one study (the mean number of studies completed per subject was 1.7). Similarly, Stewart et al (2015) find high rates of repeated participation within laboratories. Further, the majority of workers "follow" favorite requesters, and this practice is more common among the most prolific workers (Chandler et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In one study's sample, the average MTurk worker had completed a staggering 1,500 MTurk jobs, of which 300 were academic studies (Rand et al, 2014). Another recent analysis found that it takes about seven months for half of the pool of workers to be replaced (Stewart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low-quality responses and suspicious accesses (e.g., duplicate IP addresses, server farms) are blocked. To mitigate the 'super-worker problem' (i.e., a small group of workers that completes a disproportionately high share of tasks) and increase the pool of available MTurk workers (e.g., Chmielewski & Kucker, 2020;Stewart et al, 2015), we blocked the top-2% of workers from participating in our study (who complete ~34% of the tasks; Robinson et al, 2019).…”
Section: Participantsmentioning
confidence: 99%